Hukum Utilitas dalam Ekonomi Islam - Agus Tomi (Jurnal At Taajir, 2020)
Abstract Islamic banks are financial institutions that have a large influence in providing funds for the community, especially for the development of the life of a business entity. This institution plays an important role in collecting funds from the community and distributing it again to the community. Islamic banks channel excessive money to be used by other parties in need by providing assistance in the form of loans or financing, both to companies and individuals. Based on the description above, the author tries to find a description of the extent to which the concept of satisfaction (utility) in Islamic economics is compared to the concept of satisfaction (utility) in a conventional economy. Satisfaction in Islamic economics has a more comprehensive view and meaning when compared to the concept of conventional satisfaction, where in Islamic economics satisfaction is not only to meet the needs and desires to achieve mutual benefit (community welfare) but lead to obedience as God's creatures based on values Islamic. Whereas in the conventional view that satisfaction is every individual can always determine which condition is preferred between two conditions or more (completness) regardless of the health and harm. It is clear that man's desire to accumulate wealth, but also his need for preparation in the future, thus that if the spirit of always wanting more this will lead to greed and the pursuit of personal lust, then this views wealth as the "greatest test". Keyword: Hukum Utilitas, Ekonomi Islam, Conventional, Financial Institutions